Optimasi Menu Makanan Atlet Berdasarkan Jadwal Latihan Menggunakan Algoritme Genetika - Muhammad Dimas Setiawan Sanapiah; Budi Darma Setiawan; Agus Wahyu Widodo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
This research aims to solve the problem in doing food menu optimization in athletes. Where this is based on the statement of Ministry of Health that to improve the performance of Indonesian athletes in the future, it is necessary to improve and perfect the system of training and development of sports, especially in approaching and applying Science and Technology including the fulfillment of nutrition athletes. One form of development of science and technology is the genetic algorithm, where this algorithm can solve a problem related to optimization with a large search space. In the preparation of chromosomes to be used genetic algorithm using the representation of integer numbers, with crossover method used is one cut point crossover, and mutation method used is random mutation and selection process used elitism selection process. The recommendation results is the food menu for athletes for five days. While the genetic algorithm parameters in this research obtained optimal generation size of 450, the optimal population size of 70, and the combination of cr and mr optimal value is 0,5 and 0,5.